Management and health care: Narratives of pregnant adolescents in the community of Rocinha-RJ (Research, Society and Development, 2021)
This study aims to identify the meaning of pregnancy and health care from the perspective of pregnant adolescents, during prenatal care, in the geographic, cultural and social context of the Rocinha/RJ neighborhood. The methodology used was qualitative, exploratory research, based on the outlines of social research. Twenty pregnant teenagers aged between 10 and 19 years were interviewed. Data collection was through a semi-structured interview script and for the analysis, the categorical thematic content technique proposed by Bardin and Oliveira was used. Regarding the results, categories identified by the method of content analysis emerged, and one of these categories refers to the view on pregnancy and care of pregnant adolescents. Taking into account that the vision of care is always subjective and unique, these young women demonstrated that the way they are welcomed at the health unit where they perform prenatal care is the differential for starting their prenatal care and continuing their follow-up. Inserted in a context of vulnerabilities, many of these teenagers expect, through pregnancy, a form of recognition and insertion in society, of valuing and belonging, and they express, in the most varied ways, the concern and zeal for themselves and for the other (in this case the child), being promoters of their care process together with the health professionals who assist them.